A Work-Related Musculoskeletal Disorders among Physiotherapists during COVID-19 in Western Region of Saudi Arabia - Salem Mohamed, Mousa Gihan, Hawsawi Ghada, Kalantan Batool, Faraj Jude, Alqurashi Asma, Yamani Samarah, Bogari Rana, Al Mazni Waad, Al Sulami Alanoud, Al Sharif Bashyir, Yalli Shatha (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 pandemic exposed health care providers such as physiotherapists to physical injuries. Work-related musculoskeletal disorders refer to musculoskeletal injuries caused by the occupation. Objectives: The purpose of this study was to evaluate the prevalence of work-related musculoskeletal disorders among physical therapists during COVID-19 in western region of Saudi Arabia. Method: Researchers performed a cross-sectional web-based survey (questionnaire) targeting physiotherapists in western Saudi Arabia during the COVID-19 pandemic. The questionnaire composed of 3 parts: personal, occupational and physical. One hundred and ten physical therapists who replied were working at 18 public and health hospitals of the western region of Saudi Aribia, providing direct care for patients during the COVID-19 pandemic. Result: A total of 110 physiotherapists [(60%) females and (40%) males] participated in this study. The overall prevalence of work-related musculoskeletal disorders as follows: neck, shoulder, wrist/hand region (42.1%), lower back (28.9%), and neck, upper back (15.8%). The most common types of injuries were muscle strain (42.1%), pain and spasm (28.9%), and vertebral disc problem and ligament sprain (21.1%). Conclusion: The prevalence of work-related musculoskeletal disorders among physiotherapists during the COVID-19 pandemic in western region of Saudi Arabia was high in the neck, shoulder, and wrist/hand regions.